The Effect Of Non Performing Loans On Profitability In Conventional Banks Listed On The Indonesia Stock Exchange - Gunawan , Maureen Friska; Maimunah, Mutiara (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2022)
This study aims to determine the effect of non-performing loans (NPL) on the profitability of conventional banks. The population in this study were all conventional banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. This study used a purposive sampling method, and obtained 30 companies with a total sample of 90. The analysis technique in this study used the regression analysis method. simple. The results of this study indicate that non-performing loans have a negative effect on profitability